2003
DOI: 10.4141/a03-024
|View full text |Cite
|
Sign up to set email alerts
|

Semen cryopreservation: Successes and persistent problems in farm species

Abstract: Bailey, J., Morrier, A. and Cormier. N. 2003. Semen cryopreservation: Successes and persistent problems in farm species. Can. J. Anim. Sci. 83: 393-401. Artificial insemination has arguably been the most important practice contributing to the advancement of animal production. The numerous advantages of artificial insemination are augmented when the semen is cryopreserved and conserved for long periods. Unfortunately, the utility of cryopreserved semen is limited because for most mammals, even cattle, a conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 49 publications
2
75
0
6
Order By: Relevance
“…Semen cryopreservation is a well-developed technique commonly used worldwide; it extends the life of spermatozoa by decreasing sperm metabolism and toxin production, but induces partially irreversible injury to sperm membranes, which may reduce sperm motility, viability and the fertilization rate after artificial insemination [1][2][3][4][5]. Sperm damage during preservation in liquid nitrogen at -196°C has been attributed by many authors to cold shock, ice crystal formation, oxidative stress, osmotic changes, cryoprotectant toxicity and reorganizations of lipid-protein and phospholipid layers within the cell membranes [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Semen cryopreservation is a well-developed technique commonly used worldwide; it extends the life of spermatozoa by decreasing sperm metabolism and toxin production, but induces partially irreversible injury to sperm membranes, which may reduce sperm motility, viability and the fertilization rate after artificial insemination [1][2][3][4][5]. Sperm damage during preservation in liquid nitrogen at -196°C has been attributed by many authors to cold shock, ice crystal formation, oxidative stress, osmotic changes, cryoprotectant toxicity and reorganizations of lipid-protein and phospholipid layers within the cell membranes [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Short-or long-term semen preservation as a crucial pillar of animal AI comes hand in hand with numerous advantages such as genetic improvement, protection of genetic resources, decreased incidence of sexually transmitted diseases, and enhanced transportation of genetic material across countries (Bailey et al 2003).…”
mentioning
confidence: 99%
“…These interactions decrease the percentage of viable spermatozoa (Bailey et al, 2003). The present study showed that inclusion of ROM (treatment III) and its combination with GSH (treatment V) improved the viability and membrane integrity rates successfully in frozen-thawed spermatozoa.…”
Section: Discussionmentioning
confidence: 74%